Microlasers enabled by soft‐matter technology - Ta, Van Duong (2020)
Soft‐matter microlasers are an interesting part of soft‐matter photonics, which are based on liquids, liquid crystals, polymers, biological materials, and fabricated mainly by solution‐processing approaches. Soft‐matter microlasers comprehend a multitude of attractive features, including low‐cost, mechanical flexibility, wide range wavelength tunability and, in some cases, biocompatibility, and biodegradability. As such, they are recognized as versatile candidates for efficient light sources with enhanced performances and applications as ultrasensitive physical, chemical, and biological sensors. Here, the recent developments of soft‐matter microlasers are reviewed in time and the prospect in this field is provided. First, the characteristics of the representative soft‐matter microlasers are discussed with focus on their laser structures, lasing mechanisms, fabrication approaches, and gain material origins, followed by an introduction about the current cutting‐edge soft‐technologies that are applied in soft‐matter microlasers. Afterward, their potential applications as wavelength tunable sources, sensors, and displays are highlighted. Finally, the work is summarized and the prospect of soft‐matter microlasers for expanding this emerging research field is presented.